2015
DOI: 10.1007/s11284-015-1292-0
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly diversity along the elevation gradient of Eastern Himalaya, India

Abstract: The species richness pattern along spatial scales (latitudinal or elevational) forms useful tools in understanding diversity gradients and their underlying mechanisms. Understanding elevational diversity patterns of biodiversity have strong conservation implications. Himalayas are unique systems in exploring such gradients as they harbor tallest mountains in the world. Here, we explored the elevational pattern, its underlying causes, turn over rate and range size distribution of butterflies in Sikkim, Eastern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 87 publications
4
45
0
Order By: Relevance
“…This pattern corresponded with the hypothesis that indicated the species richness of insects peak at the lower elevations [28]. Similarly, butterfly species number declined with increasing elevations in the Eastern Himalaya, India due to environmental factors and habitat variables [1]. Environmental biotic factors such as abundance and quality of host plants, physical characteristic including climate, landscape and elevation, and disturbances both human activities and wildfire could influence butterfly's populations and distribution [4].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This pattern corresponded with the hypothesis that indicated the species richness of insects peak at the lower elevations [28]. Similarly, butterfly species number declined with increasing elevations in the Eastern Himalaya, India due to environmental factors and habitat variables [1]. Environmental biotic factors such as abundance and quality of host plants, physical characteristic including climate, landscape and elevation, and disturbances both human activities and wildfire could influence butterfly's populations and distribution [4].…”
Section: Discussionsupporting
confidence: 71%
“…and experiences lower temperature and more stunted vegetation as the elevation increases [33]. The previous study reported butterfly richness decreases as the altitude increases due to environmental factors and habitat variables [36,1]. Nonetheless, the mountain is an area of great biological interest as it houses high number of endemic species and is Pleistocene refuges especially for invertebrates [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, faunal assemblage along the elevational gradient is not consistent. Invertebrates like ants and butterflies (Bharti et al 2013;Acharya and Vijayan 2015) show mid-domain effects, whereas, poikilothermic vertebrates such as amphibians and reptiles exhibit monotonic decline in richness towards higher elevation (Chettri et al 2010;Khatiwada et al 2019). Birds are more complex in elevational richness pattern; they display mid domain effects in some mountains of the Himalaya (Acharya et al 2011b;Paudel and Ĺ ipoĹĄ 2014) whereas monotonic decline has been observed in the others (Basnet et al 2016).…”
mentioning
confidence: 99%
“…By contrast, β‐diversity changed in a different way; it was greater at elevations with lower temperatures, higher humidity, and lower precipitation or high temperatures, lower humidity, and higher precipitation. Most studies examining the mechanisms responsible for the distribution of butterflies have concluded that temperature and/or rainfall explain species richness (Acharya & Vijayan, 2015, Sorch et al 2003, Ribeiro et al., 2010) and have related these variables to the production of leaves (food) and butterfly physiology (Peters et al., 2016; Ribeiro et al., 2010, Bennett et al, 2015). The relationship between butterfly diversity and climate is complex, and it changes between areas and altitudes.…”
Section: Discussionmentioning
confidence: 99%